ANTIOXIDANT EFFECT OF LONGAN PERICARP EXTRACT IN PARACETAMOL-INDUCED IN RATS - Nabilah Saniyya Wahyudi; Lusiana Batubara; Endang Sri Sunarsih; Eva Annisaa' (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Oxidative stress is a condition which were free radicals harm biological molecules, like lipid, protein, and DNA. Consume paracetamol can increase oxidative stress, which can cause increased level of AST and ALT serum. Longan pericarp (Dimocarpus longan L.) is one of natural ingredients that contain phenolic and flavonoids as an antioxidant to prevent oxidative stress. This study aims to prove the effect of longan pericarp (Dimocarpus longan L.) on AST and ALT serum levels of Wistar rats induced paracetamol. Methods: Experimental research with post-test only control group design. Thirty males wistar aged 2-3 months weighing 140-250 grams randomly divided into 5 groups. Group K1 was normal control group. Group K2 was induced by paracetamol 2000 mg/kgBW. Group P1, P2, P3 were induced by paracetamol 2000 mg/kgBW administered by longan shell extract (Dimocarpus longan L.) in multilevel dose 5 mg/200 gBW, 10 mg/200 gBW, and 15 mg/200 gBW. Blood samples in each group were collected to measure AST and ALT serum levels of wistar rats. Results: There were signifficant differences groups of AST serum. There were signifficant difference groups of K1-K2 (p=0,000), K2-P2 (p=0,041), and K2-P3 (p=0,010). There were signifficant differences groups of ALT serum. There were signifficant differences groups of K1-K2 (p=0,001), K2-P2 (p=0,032), and K2-P3 (p=0,006).  Conclusions:  The longan pericarp extract can lower the AST and ALT serum levels of Wistar rats induced by paracetamol.